On an Analogy between English Nominal and Polish Aspectual Manifestations of Genericity - Klimek-Jankowska, Dorota (Proceedings of Sinn und Bedeutung, 2019)
The main goal of this study is to prove that two modal mechanisms Greenberg (2003) postulated for English indefinite singular (IS) and bare plural (BP) generics in the nominal domain are mirrored in Polish perfective and imperfective generics in the event domain. On the basis of Oosterhof’s (2006) argumentation, I justify the distinction between the GEN and the HAB intensional operators. With this distinction in mind, I associate the combination of HAB+perfective aspect as exemplifying the same kind of an ‘in virtue of’ modality as Greenberg postulates for the combination of GEN+IS. In the same manner, I claim that both the combination of GEN+BP and the combination of HAB+imperfective aspect exemplify either ‘descriptive’ or ‘in virtue of' modality.